In-situ polymerization of PPy/cellulose composite sponge with high elasticity and conductivity for the application of pressure sensor. (December 2017) - Luo, Mengying; Li, Mufang; Li, Yuqin; Chang, Kangqi; Liu, Ke; Liu, Qiongzhen; Wang, Yuedan; Lu, Zhentan; Liu, Xue; Wang, Dong
Abstract: In this study, the pressure sensor of polypyrrole/cellulose (PPy/C) sponge with outstanding electrical conductivity, elasticity and flexibility was prepared by a simple and environmentally friendly method. The original cellulose sponge was obtained by freeze-drying of cellulose/NaOH/urea solution under an optimum condition. To get a conductive sponge, the pyrroles have been in-situ chemical oxidative polymerized on cellulose sponge. The effects of bath ratio and reaction time on the structures, morphologies and electrical resistances of PPy/C composite sponges were analyzed to decide the optimum process parameters. Moreover, a test device consisted of pressure meter and ohmmeter was designed to investigate the properties of the PPy/C sponge sensor. It exhibited the excellent conductivity, sensitivity under a very small pressure (0–5 kPa) and good repeatability. The results demonstrated that the PPy/C sponge could be a promising candidate for pressure sensor to test external stimulus. Highlights: PPy/Cellulose composite sponge was prepared by a simple and environmental friendly method. PPy/Cellulose composite sponge exhibited excellent electrical conductivity, sensitivity and repeatability. The PPy/C sponge could be a promising candidate as pressure sensor to test the external stimulus.